Cultural and creative industries and border effects: an approach for Ukraine under war conditions. - Arauzo-Carod, Josep-Maria; Moroz, Serhiy (Journal for Cultural Research, 2025)
This paper analyses border effects on the evolution of Cultural and Creative Industries (CCIs) during 2013‒2020 when Russia invaded some areas of Ukraine (2014). As most empirical evidence on CCIs refers to OECD countries, this paper contributes to the literature by focusing on a mid-income European country suffering from a war conflict. Our results are meaningful for understanding the positive contribution of CCIs to economic activity in these circumstances and suggest that i) this effect applies to all industries except CCIs, and that ii) proximity to conflict regions counterbalances previous positive effects. Overall, we conclude that CCIs should play a major role in the recovery of the Ukrainian economy once post-war plans can be implemented.